A mini review of the recent progress of electrode materials for low-temperature solid oxide fuel cells. Issue 8 (14th February 2023) - Hu, Shiming; Li, Jin; Zeng, Yu; Pu, Jian; Chi, Bo
Abstract : This review provides the recent progress of electrode modifications for low-temperature solid oxide fuel cells. The atomic control strategy and morphology decoration of electrodes to improve the electrochemical properties of LT-SOFC are discussed. Abstract : Lowering the operating temperature (450–650 °C) of solid oxide fuel cells (SOFCs) faces the intrinsic challenge of sluggish electrode reaction kinetics in the low temperature (LT) range. To accelerate the electrode reaction rate, many efforts have been put into the optimization of electrode composition and morphology. In this review, we have summarized recent developments of LT-SOFC electrodes, including anode and cathode materials. For anode performance improvement, the internal structure design, fine anode structure, reforming layer addition, and in situ exsolution techniques are introduced and their related functionalities are also explained, respectively. While for the cathode, we focus on the perovskite-type materials because of their superior catalytic performance and relatively good stability. The optimization of perovskite composition, including A site alkali or alkali-earth metal doping and B site variable–valence transition metal doping, is discussed in detail based on their effects on oxygen reduction reaction (ORR). Besides, nanostructure assembly and 3D morphology design are also recent hotspots for cathode research. Finally, we also propose several research directions in this field, hoping to provide guidelines for future research.